Perturbations in upper tropospheric easterlies and Bay cyclones
Pertu rbat ions in th e form of large amplitude troughs or dosed circu lation s are absen ted to develop in the weak upper tro posph eric easterlies at 200 and 100 hPs levels over no rthwest Pacific am! adjoining Indi an Ocean. Occasionally, these are 2 to 3-C colder than their immediate enviro nme nt. These systems are observed 10 propagate downwards durina their westwa rd tr aversal : while ove r 500 h Ps th ese in teract with and activate the lower troposph eric cyclonic circ ula tion to intensify into a depression/cyclonic stem